2018
DOI: 10.7759/cureus.3119
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific Knowledge of Diabetes and Its Management Among Patients Visiting Outpatient Clinics in Faisalabad, Pakistan

Abstract: Introduction: Diabetes mellitus is an emerging public health concern. The aim of this study was to assess the gender-specific knowledge of patients about diabetes mellitus, its complications, and its management.Methods: A cross-sectional study was conducted in outpatient clinics of Faisalabad, Pakistan, from November 2017 to March 2018. Consecutive patients with diabetes, aged >18 years, were administered a validated questionnaire related to knowledge of diabetes, its complications, and its management. An anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…Similarly, many studies conducted in diverse population have shown that girl and women performed better than boys and men regarding diabetes prevention practices. However, this contradicts the findings of [28] who reported no significant differences between male and females regarding their basic knowledge and preventive practices.…”
Section: Discussioncontrasting
confidence: 96%
“…Similarly, many studies conducted in diverse population have shown that girl and women performed better than boys and men regarding diabetes prevention practices. However, this contradicts the findings of [28] who reported no significant differences between male and females regarding their basic knowledge and preventive practices.…”
Section: Discussioncontrasting
confidence: 96%
“…Sociodemographic factors, such as marital status, may be overly generic when predicting an individual's DM medication awareness. A study revealed no correlation between gender and low awareness of DM medication ( 43 ). However, males were reported to be less aware of DM than females were ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…A cross sectional study was conducted in different hospitals of Gujrat, Pakistan. 153 multigravida females with the history of frequent miscarriages, abortions (8), GDM (9) were included in this study and data was collected from them after taking informed consent, using self-structured questionnaire through convenient sampling. Females diagnosed with DM before 1st pregnancy (1), primigravida, history of macrosomic baby and stillbirth (10), with polycystic ovarian syndrome, diagnosed liver, cardiovascular and kidney disease (11), who did not receive a postpartum diabetes assessment were excluded from the study (12).…”
Section: Methodsmentioning
confidence: 99%